Sensitivitätsanalyse des 3-Rollen-Schubbiegens auf Basis der Finite Elemente Methode - Vatter, Peter (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)
The three-roll-push-bending process is a kinematic bending process, which can be used to manufacture almost arbitrarily curved 3-dimensional tube components. A disadvantage compared to conventional tool-bound bending processes is the lower repeat accuracy. This book informs operators as well as machine designers about the causes of process deviations. Additionally, the cause-effect relationship between the input parameters and the geometry parameters is described. By this, measures can be deduced to enhance the process robustness in industrial applicatio